ATURAN HUKUM PIHAK MANDALA MULTIFINANCE TARIK KENDARAAN KONSUMEN KREDIT MACET - Miranda Miranda (IAIN Padangsidimpuan, 2022)
Taking a vehicle due to arrears in rent installments by leasing or as an agent for a financial institution is often a well-known event from various media reports and experiences in the community. The problem in this research is how to implement the registration of fiduciary guarantees for motor vehicle financing companies based on decision number ; 1/Pdt.G.S/2022/PN.Kla. and what is the legality of the withdrawal of motorized vehicles carried out by financial institutions based on decision number ; 1/Pdt.G.S/2022/PN.Kla. The lawsuit was carried out by a panel of judges who were competent in Verstek. The form of legal protection provided to consumers who experience motor vehicle withdrawals by the leasing party through the ministry of finance has issued a new regulatory breakthrough which is included in the Minister of Finance Regulation Number 130 of 2012 concerning registration of fiduciary guarantees for finance companies, which prohibits leasing companies from forcibly withdrawing vehicles. motorized on the road. Based on the results of the study, the implementation of fiduciary guarantee registration for motor vehicle financing companies includes submitting a fiduciary guarantee registration application, checking the completeness of the guarantee registration application requirements, recording in the Fiduciary Register Book, and issuing a Fiduciary Guarantee Certificate